The Negative Impact of Social Media on Youth’s Social Lives - Nooriallai Noori; Ajmal Sayes; Gulaqa Anwari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The results of numerous scientific researches in developed countries shows that the content produced by social media has a significant impact on the behavior and lifestyle of young people, especially in developing countries such as Afghanistan; But the main problem is that there has been no serious awareness and cognition about the harmful impact of social media content on young people on developing countries, which is comprehensively discussed in this research paper. The general purpose of this paper is to provide information and create awareness about the negative impact of social media on youth's social behavior through content analyses and qualitative research. Social Media refers to different types of platforms or applications such as WhatsApp, Facebook, TikTok, Twitter, LinkedIn, YouTube, etc. through which people share information and use it as a communication resource.This study has specifically addressed the basic questions that How social media changes youth's social behavior and what are the main factors which because social behavior changes in youths by using social media and what are the negative impact of social media on youth's social lives by using reliable resources.  Even though social media sites and platforms have more advantages and positive impacts and provide a lot of communication, business, and entertainment opportunities, it leads to social isolation, anxiety, depression, cyberbullying, sexuality, loss of privacy, terrorism, etc.  It reduces the number of face-to-face interactions among the youth because they normally spend most of their time on online social platforms. The result of this research shows that social media leads to social isolation and this can cause several effects such as physical, emotional, mental, and psychological issues on youths. This can lead to depression, anxiety, and many other problems.